2013
DOI: 10.1172/jci67008
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 blockade synergizes with IL-2 therapy in reinvigorating exhausted T cells

Abstract: The inhibitory receptor programmed cell death 1 (PD-1) plays a major role in functional exhaustion of T cells during chronic infections and cancer, and recent clinical data suggest that blockade of the PD-1 pathway is an effective immunotherapy in treating certain cancers. Thus, it is important to define combinatorial approaches that increase the efficacy of PD-1 blockade. To address this issue, we examined the effect of IL-2 and PD-1 ligand 1 (PD-L1) blockade in the mouse model of chronic lymphocytic choriome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
210
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(223 citation statements)
references
References 61 publications
11
210
1
1
Order By: Relevance
“…PD-1 blockade has been used in combination with various therapeutic agents to improve immunotherapeutic effects, such as another immunosuppressive blocking antibody cytotoxic Tlymphocyte antigen-4 (CTLA-4) mAb, 14 the immune stimulating factor IL-2, 35 the blocking antibody of human epidermal growth factor receptor-2 (HER-2 / ErbB-2), 36 and radiotherapy. 37,38 In this study, we have explored two strategies to improve therapeutic efficacy of the high-profile PD-1 blocking mAb treatment and the potential side effects associated with PD-1 blockade: (a) an alginate hydrogel delivery system to deliver therapeutic agents to tumor local regions; (b) in combination with celecoxib.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 blockade has been used in combination with various therapeutic agents to improve immunotherapeutic effects, such as another immunosuppressive blocking antibody cytotoxic Tlymphocyte antigen-4 (CTLA-4) mAb, 14 the immune stimulating factor IL-2, 35 the blocking antibody of human epidermal growth factor receptor-2 (HER-2 / ErbB-2), 36 and radiotherapy. 37,38 In this study, we have explored two strategies to improve therapeutic efficacy of the high-profile PD-1 blocking mAb treatment and the potential side effects associated with PD-1 blockade: (a) an alginate hydrogel delivery system to deliver therapeutic agents to tumor local regions; (b) in combination with celecoxib.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of how to rescue exhausted CD8 ϩ T cells may be critical to decreasing the incidence of reactivation and reinfection, even after vaccination. By blocking PD-1-mediated inhibitory signals and supplementation with additional IL-2, others reported that exhaustion is a reversible phenotype of CD8 ϩ T cells (26,(35)(36)(37). For instance, a decrease in the production of reactive oxygen intermediates by macrophages mediated by PD-1-bearing CD4 ϩ and CD8 ϩ T cells allows increased intracellular pathogen load in leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, administration of low-dose IL-2 combined with PD-L1 blockade has been demonstrated to decrease inhibitory receptor expression and viral load in a chronic murine LCMV model as IL-2 treatment may foster the generation of a pool of CD44 hi PD-1 int T-cells that are more responsive to PD-L1 blockade. 49 Thus, novel therapeutic strategies, exploring the generation of more PD-1 neg and PD-1 int cells, instead of PD-1 hi cells to increase the susceptibility to PD-1/PD-L1 blockade, are clearly needed.…”
Section: Discussionmentioning
confidence: 99%